The determinants of consumer behaviour of students from Brno when purchasing organic food - Jana Švecová; Pavla Odehnalová (Review of Economic Perspectives, 2019)
The subject of this paper is the analysis of consumer behaviour in the organic market, focused on the behavior of students from Brno. Our study brings information which can potentially be used for further research and will also be useful for organizations with a practical interest in the production sale and distribution of organic food. To investigate the influence of the various factors was used the extended model of Theory of Planned Behaviour (TPB). In the current concept, there is no research in the Czech Republic that would apply the approach of Yadav and Pathak (2016) to examine of consumer behaviour on the sample of students, i.e. young Czech generations who are a potential target group. The theoretical part deals with the concept of consumer behaviour, based on the findings of the latest studies, dealing with this topic. In the practical part, the own research is presented, realized on a sample of 403 young consumers, studying in the second largest city of the Czech Republic, the city of Brno. In the Czech Republic, the young consumer is influenced mainly by factors such as personal attitude and subjective norms. Limitations of this study are the fact that in our questionnaire we were interested in how the consumer viewed the purchase of organic food in general and not how they view the purchase of individual organic products and that the research may be limited by the fact that the questionnaire was aimed solely at the younger generation of consumers studying in Brno, the second largest city in the Czech Republic. The behaviour of the younger generation has received little investigation, and in the Czech Republic, there is a lack of research on the behaviour of this sector.
Keywords: M31; Q21; C1; 330; Consumer behaviour; organic food; theory of planned behaviour